Awareness and Diffusion of TSA as Creative Governance Tool among Lagosians - Uche Chuks-Enwerem, Chuks Odiegwu, Lai Oso, Lanre Amodu & (Covenant Journal of Entrepreneurship, 2019)
This study examined public awareness, and of Treasury Single Account (TSA) a creative and innovative governance tool among Nigerians. Many previous studies on TSA have focused mainly on assessing the negative and positive effects and implications of the initiative, while little has been done to address the awareness and diffusion of the innovation among the people during and after its introduction. This study therefore sought to examine how the public became aware of the policy and how the innovation was diffused within the time of review. Survey was adopted to generate primary data while structured questionnaire was administered to 120 respondents randomly selected from among postgraduate students and lecturers of University of Lagos (with 96% return rate). Random sampling was informed by the need to give every member of the target group a chance to be selected while the choice of University of Lagos was informed by the need to involve educated and knowledgeable individuals with sufficient knowledge of the subject matter; university environment was selected purposively to simplify the process of reaching the respondents at one place without sacrificing adequate representation. Data was analysed using simple frequency and percentages. Findings show that the citizens’ knowledge of the introduction of the governance instruments was slow but steady within the first three months; many of the citizens were positively disposed to TSA based on their belief that it would bring transparency and curb financial corruption. The paper recommends that the introduction of new ideas into governance, particularly technologically driven initiatives, needs to be adequately publicised through the media to enable a good majority of the citizens to understand and buy into it as citizens’ acceptance and adoption are paramount.